Bursting heart syndrome; a rare case of aortocaval fistula repair - Kareem, Talha; Ahmed, Muhammad Adeel; Nihal, Faizan; Ehsan, Omer; Khan, Iqbal (Journal of the Pakistan Medical Association, 2023)
In this case report we will discuss a case of a 47-year-old woman who presented with abdominal pain, nausea, oliguria and right heart failure. A Computed Tomography (CT) aortogram revealed a fistulous abdominal aortic aneurysm. The objective of this study is to discuss the haemodynamic changes regarding aortocaval fistula and consider various management options. A literature search was undertaken on PubMed using appropriate search terms. Case series and reviews reporting presentation, diagnosis and operative management of aortocaval fistula were selected and discussed. We reached a conclusion that early identification improves surgical planning and reduces mortality. Major abdominal arteriovenous fistula repair appears to be a safer and more successful therapy with positive short and midterm outcomes. Aortocaval fistula care requires a more extensive patient series, so even better conclusions can be drawn. Keywords: Inferior vena cava; Aortocaval fistula; Abdominal aortic aneurysm; Open aneurysm repair; EVAR; Hybrid abdominal aortic aneurysm repair.